2016
DOI: 10.1371/journal.pone.0163916
|View full text |Cite
|
Sign up to set email alerts
|

Suitability Analysis and Projected Climate Change Impact on Banana and Coffee Production Zones in Nepal

Abstract: The Government of Nepal has identified opportunities in agricultural commercialization, responding to a growing internal demand and expansion of export markets to reduce the immense trade deficit. Several cash crops, including coffee and bananas, have been identified in the recently approved Agriculture Development Strategy. Both of these crops have encouraged smallholder farmers to convert their subsistence farming practices to more commercial cultivation. Identification of suitable agro-ecological zones and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 49 publications
0
42
0
3
Order By: Relevance
“…The WorldClim dataset's resolution of 1000 m is not able to reflect the surface accurately, especially in regions with steep slopes and narrow valleys, nor does it represent microclimatic situations [21]. Despite these limitations, the WorldClim dataset is the best-developed dataset available for Nepal [20,42,43,53,54]. Moreover, a study by Glotter et al [55] showed that, once a correction is applied, the results of general circulation models and regional climate models are indistinguishable in all four scenarios.…”
Section: Limitations Of the Date Setmentioning
confidence: 99%
“…The WorldClim dataset's resolution of 1000 m is not able to reflect the surface accurately, especially in regions with steep slopes and narrow valleys, nor does it represent microclimatic situations [21]. Despite these limitations, the WorldClim dataset is the best-developed dataset available for Nepal [20,42,43,53,54]. Moreover, a study by Glotter et al [55] showed that, once a correction is applied, the results of general circulation models and regional climate models are indistinguishable in all four scenarios.…”
Section: Limitations Of the Date Setmentioning
confidence: 99%
“…Projections for Puerto Rico are also dire; by 2071-2099, only 24 km 2 are projected to be suitable for coffee production [62]. Projected reductions in suitable coffee growing areas by 2050 in many other countries have also been reported [63][64][65].…”
Section: Climate Impacts On Current Coffee Production Areasmentioning
confidence: 99%
“…A number of studies on species suitability account for univariate dissimilarity among covariates by restricting extrapolation to areas where predictors are within the reference range of individual covariates (Li et al 2016;Ranjitkar et al 2016). The multivariate environmental similarity surfaces (MESS;Elith et al 2010) is one of widely used algorithm to identify the areas in the projection domain where values of at least one individual covariate are beyond the reference range (Li et al 2016;Ranjitkar et al 2016). However, MESS is limited because it only accounts for the range of individual variables thus overlooking the multivariate combinations of covariates (Mesgaran et al 2014).…”
Section: Generating Esimentioning
confidence: 99%
“…Bottom-up geospatial approach for delianating extrapolation domains involve a degree of extrapolation beyond the limits of observed covariate space due to spatial-temporal biases in trial site data and environmental heterogeneity (Elith et al 2010;Zurell et al 2012;Ranjitkar et al 2016). Two types of extrapolation can occur: (1) the range of values (minimum/maximum) for individual predictors in the projection domain are beyond that in the reference sites (Novelty type 1, NT1); or (2) predictors exhibit unique combinations (novel correlation structure) not observed in the reference domain (Novelty type 2, NT2) (Zurell et al 2012;Owens et al 2013;Mesgaran et al 2014).…”
Section: Introductionmentioning
confidence: 99%